EFEKTIVITAS FUNGSI DPD DALAM PEMERINTAHAN DAERAH KEISTIMEWAAN YOGYAKARTA: PERSPEKTIF FIKIH SIYASAH - Adiwilaga, Rendy; Muthmainah, Della Siti; Wulandari, Tiarasanti; Riaji, Isnandi Abdul Rozak (Mitsaqan Ghalizan, 2025)
The pros and cons of sand mining activities in Kali Progo are complex issues that require a holistic approach in solving them. The community's rejection of mining activities is motivated by concerns about environmental damage that has the potential to threaten the sustainability of the ecosystem and the survival of local communities. In this context, DPD RI Yogyakarta as a regional representative institution plays a strategic role in mediating and following up on community aspirations. This study aims to analyze the effectiveness of DPD RI Yogyakarta's role in handling the sand mining conflict through the theoretical approach of organizational effectiveness from Martani and Lubis which includes three dimensions: target, source, and process approaches. The method used in this research is descriptive qualitative with purposive sampling technique, located in DPD RI Yogyakarta. Data collection is done through direct observation, Focus Group Discussion (FGD), and document study. The results showed that DPD RI Yogyakarta has effectively carried out its role as a mediator in this conflict. This is evidenced by the success of the institution in accommodating aspirations, identifying the main issues, and facilitating dialog forums between stakeholders that produce compromise solutions. From the perspective of fikih siyasah, the role of DPD reflects the implementation of the principle of siyasah syar'iyyah which emphasizes the importance of protecting the public good (maslahah 'ammah), involving the people through deliberation (shura), and managing natural resources fairly, sustainably, and trustworthily. Thus, the role of DPD RI Yogyakarta is not only constitutionally relevant, but also in line with the principles of Islamic political ethics.